Hexafluorosilicate coordination to the antitumour copper(II) salicylaldehyde benzoylhydrazone (H2L) system: single-crystal X-ray structure of [{Cu(HL)H2O}2SiF6]·2H2O - Ainscough, E.W. (2014)
Inorganica Chimica Acta